Inorganic element doped high-uniformity mineral polymer and preparation method thereof
The preparation of highly uniform mineral polymers incorporated with inorganic elements through mineral polymerization technology and 3D printing technology, solving the problem of lack of standard substances in situ analysis of micro-domain, achieving high uniformity and accurate analysis of samples, and is suitable for rare earth mineral exploration.
Patent Information
- Application Number
- CN202510418893.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2045-04-03
AI Technical Summary
现有技术中微区原位分析标准物质匮乏,样品基体适用性和微区均匀性差,限制了稀土矿产资源勘探开发的深入研究。
Mineral polymerization technology combined with 3D printing technology is used to prepare highly uniform mineral polymers incorporated inorganic elements. By controlling the elemental composition and distribution of aluminosilicate minerals, and combining laser erosion inductively coupled plasma mass spectrometer for analysis, the customized molding and automated production of samples are realized.
The micro-region uniformity and analysis accuracy of the sample are improved, matching with the actual sample matrix is achieved, and the requirements of in-situ micro-region analysis are met. The relative standard deviation is between 3.82% and 7.35%, achieving the measurement accuracy of the traditional molten glass method.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to a highly uniform mineral polymer doped with inorganic elements and a preparation method thereof, belonging to the technical fields of 3D printing and mineral polymerization. Background Art
[0002] As a strategic mineral resource with special properties, rare earth materials are widely used in military, industrial, high-tech and other fields, and have the title of "industrial vitamin". Since the 1950s, by using relatively traditional geochemical research techniques for rare metals and rare earth deposits, China has obtained a large amount of data in the fields of rare earth reserves and ore-forming research, and thus established its international status in rare earth mineral resources. However, after decades of exploration and exploitation, there are fewer and fewer mineral resources with shallow burial, large scale and simple prospecting conditions. With the rapid development of China's economy, the demand for mineral resources is increasing continuously, and the strategic resource status of rare earth materials as "China's dominant minor metals" has become increasingly prominent.
[0003] In recent years, modern micro-area in-situ analysis techniques represented by the combined technique of large-scale secondary ion mass spectrometry (SIMS) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) can reveal important information on subtle changes masked by conventional bulk analysis, and have become the core technical support for solving many major scientific problems. However, with the development of in-situ micro-area analysis techniques, the lack of micro-area analysis reference materials has become a bottleneck restricting the further in-depth development of related research and has received wide attention in the scientific community. In the development of micro-area analysis reference materials, the main challenges include the applicability of sample matrices, the micro-area uniformity of samples, and the accurate calibration of micro-area reference materials. In the past ten-odd years, in-situ micro-area analysis techniques, as new means in the exploration, development and utilization of strategic mineral resources, have received extensive attention from geological experts at home and abroad. However, due to factors such as the shortage of in-situ micro-area reference materials and the lack of reference material development techniques, the development of related research faces a series of technical bottlenecks. There is an urgent need to establish in-situ micro-area analysis techniques with higher accuracy and clearer traceability and to develop micro-area analysis reference materials to provide more effective methodological support for the exploration, development and utilization of strategic mineral resources.
[0004] Geopolymer technology uses natural minerals or solid waste and artificial aluminosilicate compounds as raw materials to prepare a three-dimensional network polymer gel of silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra, and its product is called geopolymer (GP). The geopolymerization reaction consumes the water in the alkali activator to partially dissolve the solid aluminosilicate raw materials, generating silicon and aluminum tetrahedra. At high pH values, amorphous aluminosilicates dissolve rapidly, forming a supersaturated aluminosilicate solution, which then forms a gel. After gelation, the connectivity of the gel network increases, rearranging and recombining to form a new three-dimensional aluminosilicate network. The gel forms a large network structure through polycondensation, and this process releases the water consumed during the dissolution process. This rearrangement process of the gel network determines the microstructure of the resulting polymer. This structure composed of 4- and [AlO4] 5- tetrahedra is similar to natural minerals and is more conducive to achieving matrix matching with actual samples.
[0005] In addition, as a new forming technology, 3D printing, known as the "third industrial revolution", is rapidly attracting more and more attention. By slicing a digital model and stacking materials layer by layer to form a solid model. With this stacking method, 3D printing has great advantages in manufacturing components with complex structures. Due to its advantages such as high raw material utilization rate, customized forming, and low cost, it has broad application prospects. Its basic principle can be summarized as laminated additive manufacturing. This process decomposes the traditional macroscopic forming process into a forming process that occurs simultaneously on a surface-by-surface and point-by-point basis, which helps to achieve microscopic control of the forming process and is of great help in improving the uniformity of the formed samples. Summary of the Invention
[0006] The object of the present invention is to provide a highly uniform mineral polymer incorporated with inorganic elements and its preparation method. By using geopolymer technology and artificially adding target elements, imitating the element composition and distribution of common aluminosilicate minerals, corresponding bulk reference materials of the system are prepared to achieve the purpose of matching the complex matrix of the target mineral. Combining with 3D printing technology, a customized forming process for the above-mentioned reference materials is realized, and the automated production of the reference materials is achieved.
[0007] The preparation method of the highly uniform mineral polymer incorporated with inorganic elements provided by the present invention includes the following steps:
[0008] S1. Determine the dosage of each raw material according to the system of equations shown in formula (1);
[0009]
[0010] In the formula, n(NaOH) represents the molar amount of sodium hydroxide, n(Waterglass) represents the molar amount of water glass, n(metakaolin) represents the molar amount of metakaolin, n(Na) / n(Al) represents the molar ratio of sodium (Na) element and aluminum (Al) element in the system, and n(Si) / n(Al) represents the molar ratio of silicon (Si) element and aluminum (Al) element in the system;
[0011] M represents the modulus of the alkali activator, and this parameter is used to describe the molar ratio of the corresponding oxides of Si and Na in the alkali activator. Its calculation formula is as follows:
[0012] M = n(SiO2) / n(Na2O)
[0013] S2. Under the condition of stirring, the alkali activator solution is added to the mixture of metakaolin and the mother liquor of target elements in multiple times, and the obtained slurry is solidified.
[0014] In the method of the present invention, by giving three key ratios of M, n(Na) / n(Al), and n(Si) / n(Al), the unique proportion of four components can be solved, and the weighing mass can be calculated according to the relative molecular mass. In addition, the addition amount of pure water (MilliQ) is used to simulate the mass of water introduced by the mother liquor of elements, and this content needs to be calculated through the water loss of the sample during drying and the target concentration.
[0015] Preferably, n(Na) / n(Al) = 1.28, n(Si) / n(Al) = 2.50, M = 1.83.
[0016] In the preparation method of the present invention, the target elements include scandium, yttrium and lanthanide rare earth elements, including lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium.
[0017] In the preparation method of the present invention, in step S2, after the addition of the alkali activator solution is completed, it is stirred at a rotation speed of 400 - 600 r / min for 26 - 38 h.
[0018] In the preparation method of the present invention, in step S2, before the solidification, the slurry is degassed; preferably vacuum degassing;
[0019] The time of the vacuum degassing is 15 min, and its vacuum degree is below 0.01 Mpa.
[0020] Through the degassing treatment, defects such as air bubbles introduced during the stirring of the sample are excluded, so as to reduce the air bubbles in the sample after solidification;
[0021] By comparing the degassing effects of vacuum degassing, ultrasonic degassing, and static setting methods, it was found that the vacuum degassing effect was much better than the other two degassing methods. It was speculated that this phenomenon was related to the smaller particle size of the raw materials. For similar powders, during the wetting process, it was mainly hindered by the gas adsorbed on the powder surface. Therefore, when the air pressure was reduced, the gas on the powder surface was discharged and completely wetted. This avoided the agglomeration of particles during the curing process, thus greatly improving the elemental uniformity of the cured sample. Therefore, during the two processes of discharging gas from the powder sample, that is, during the mixing stage of the elemental mother liquor and metakaolin powder and after the sample was stirred, it was necessary to carry out the corresponding vacuum degassing (dissolution) steps.
[0022] In the preparation method of the present invention, in step S2, the curing method is 3D printing molding, preferably the direct writing molding process.
[0023] The characteristics of the 3D printing molding lie in additive manufacturing, that is, by gradually adding materials point by point, line by line, and layer by layer on the substrate and curing them on the printed sample, a three-dimensional entity is finally formed. When applied to the geopolymer system, it is different from the traditional integral injection molding, but instead forms each solid unit. The original centimeter-level long curing scale is divided into multiple short-time molding processes of hundreds of micrometers, thereby suppressing the phenomenon of differentiation between the surface layer and the inner layer in the sample, and thus achieving the overall uniformity of the sample.
[0024] Based on the reaction mechanism of the geopolymer system involved in the present invention, the direct ink writing (DIW) technology can meet the requirements of its 3D printing. As a common technology for 3D printing ceramics, the DIW technology extrudes the ceramic slurry out of the barrel through an extrusion device, extrudes it through a nozzle at a specified position, and moves on a two-dimensional plane according to the path setting. After completing the sliced pattern of this layer, the barrel is raised or the platform is lowered to a suitable position to perform the printing of the next layer, and so on until the printing is completed to obtain a three-dimensional entity.
[0025] The entire process of the direct writing molding process depends on the rheological properties of the slurry, that is, during the extrusion process, it transforms into a fluid under the action of external force and quickly "solidifies" after extrusion to maintain the shape without collapsing, so as to retain the molded shape to the greatest extent and separate the extruded part from the subsequent slurry. And, in order to make the most of the characteristics of the geopolymer system losing water and curing, the present invention uses the SYNO 4070 ceramic printer (Henan Yuanchuang Gaoke Technology Co., Ltd.), which has an environmental heating function and can turn on the internal hot air circulation during the curing process, so that the extruded slurry can lose water faster. And, a motor-driven stirring screw is installed at the extrusion head part, which can provide shear force to temporarily reduce the kinematic viscosity of the gel system, so as to extrude more smoothly.
[0026] In the preparation method of the present invention, the 3D printing is carried out within 4 hours after the slurry is stirred for at least 28 hours.
[0027] In the initial stage of the geopolymerization reaction, the tetrahedra are gradually dissolved by the alkali activator in the system to form a loose gel network. As the dissolution amount gradually increases, the connectivity of the gel network increases and the free water decreases, resulting in a gradual increase in viscosity and finally solidification. In order to quantitatively describe the change of the rheological properties of the slurry in this process and thus determine the appropriate printing time and viscosity, the present invention uses a ViscoQC100-H viscometer produced by Anton Paar to monitor the change of the sample viscosity with time, using a V73 blade, and the maximum test viscosity is 20.48 Pa·s (200 r min -1 ), and the accuracy is one-thousandth. It is found through experiments that in order to keep the slurry in the extrusion head without leakage at an appropriate viscosity and at the same time to dissolve as many raw material particles as possible, the most suitable starting time for printing should be controlled between 26 h and 38 h after the start of sample stirring. After that, the viscosity of the sample rises sharply and it will be difficult to maintain fluidity until printing is completed.
[0028] In the preparation method of the present invention, the LA-ICP-MS (laser ablation inductively coupled plasma mass spectrometer) method is used to test the uniformity of the mineral polymer.
[0029] The LA-ICP-MS can directly analyze solid samples under quasi-nondestructive conditions and obtain in-situ element concentration information with a certain spatial resolution. In order to study the element composition in the nodule samples, the present invention uses a 193 nm and 213 nm laser ablation system for the analysis of the total element content.
[0030] Based on the geopolymerization theory, combined with 3D printing technology, and taking the measurement results of Laser ablation Inductively Coupled Plasma Mass Spectrometer (LA-ICP-MS) as the evaluation criterion, supplemented by auxiliary characterization means such as laser particle size scattering, X-ray diffractometer, and thermogravimetric analyzer, a series of related studies on the raw material composition, pretreatment process, important ratio parameters, mixing scheme, and curing process parameters in the geopolymerization system have been carried out. A research method for developing reference materials based on geopolymerization technology has been established, realizing the 3D printing of geopolymers with artificially added target elements at room temperature, and the uniformity of the added elements can meet the requirements of micro-area in-situ analysis. Micro-area element concentration imaging has been performed on the prepared samples. The results show that the micro-area uniformity is good, and the relative standard deviation in LA-ICP-MS measurement is 3.82%-7.35% (after internal standard correction), reaching the same measurement accuracy level as the standard samples prepared by the fused glass method. Relevant measurement methods have been designed according to the measurement requirements, shortening the measurement time.
[0031] Specifically, the present invention has the following beneficial technical effects:
[0032] The present invention provides a highly uniform geopolymer with inorganic element incorporation and its preparation method. The reaction conditions are mixed in a liquid state and formed at room temperature, which helps the incorporated elements to be uniformly mixed in the matrix. The surface dissolution-gel rearrangement process in the geopolymerization reaction increases the connectivity of the gel network and forms a gel network that restricts the movement of cations, thereby weakening the element segregation during the curing process. The above advantages improve the uniformity of the finally cured samples. The samples (GP-M4-LV-FINAL, Example 3) after optimizing the process route are verified to have good internal uniformity by LA-ICP-MS analysis, and the relative standard deviation in LA-ICP-MS measurement is 3.82%-7.35% (after internal standard correction), which is at the same level as the measurement accuracy of the NIM-4 samples prepared by the traditional fused glass method.
[0033] The basic unit of the geopolymerization reaction of the present invention, [SiO4] in the system 4- and [AlO4] 5- are the same as the basic composition units of natural minerals, which is beneficial to achieving matrix matching with actual samples. It is beneficial for the quantitative determination of rare earth minerals and the indication of ore depositology in subsequent actual analysis scenarios. Description of the Drawings
[0034] Figure 1 It is the image and signal fluctuation of nodules in GP-3 in Example 1 of the present invention during the LA-ICP-MS analysis process.
[0035] Figure 2 It is the appearance diagram of the GP-2 sample in Embodiment 1 of the present invention.
[0036] Figure 3 It is the state diagram of the slurry after sequentially adding an alkali activator in Embodiment 2 of the present invention.
[0037] Figure 4 It is the surface morphology of the sample obtained by curing through three degassing methods in Embodiment 2 of the present invention.
[0038] Figure 5 It is the line scan signal fluctuation of three degassing methods and NIM-4 in Embodiment 2 of the present invention.
[0039] Figure 6 It is the longitudinal section of the cured sample in Embodiment 2 of the present invention.
[0040] Figure 7 It is the signal fluctuation of the internal sample of the Vacuum group in LA-ICP-MS in Embodiment 2 of the present invention.
[0041] Figure 8 It is the external view of the SYNO 4070 ceramic printer.
[0042] Figure 9 It is the photo of the 3D printer accessories (a) extrusion head (b) stirring screw.
[0043] Figure 10 It is the coating and curing conditions of GP-M1 to M10 in Embodiment 2 of the present invention.
[0044] Figure 11 It is the signal fluctuation of the La element in the GP-M1 to M10 slurries in the LA-ICP-MS analysis in Embodiment 2 of the present invention.
[0045] Figure 12 It is the graph of the slurry viscosity changing with the stirring duration in Embodiment 2 of the present invention.
[0046] Figure 13 It is the schematic diagram of the gcode slicing in Embodiment 2 of the present invention.
[0047] Figure 14 It is the LA-ICP-MS signal stability of GP-M4-HV and GP-M4-LV in Embodiment 2 of the present invention.
[0048] Figure 15 It is the sample ring and the fitted sample in Embodiment 2 of the present invention.
[0049] Figure 16 It is the schematic diagram of the sample uniformity analysis strategy in Embodiment 3 of the present invention.
[0050] Figure 17 It is the overall micro-region imaging diagram of the GP-M4-LV-FINAL sample in Example 3 of the present invention.
[0051] Figure 18 It is the local micro-region imaging diagram of the GP-M4-LV-FINAL sample in Example 3 of the present invention. Detailed implementation manners
[0052] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0053] Unless otherwise specified, the materials, reagents, etc. used in the following examples can all be obtained from commercial channels.
[0054] The following examples use 193nm and 213nm laser ablation systems for the analysis of total elemental content. Among them, the model of the 213nm laser ablation system is LSX213-G2+, and the manufacturer is CETAC Technologies, USA. The 213nm laser is excited by a five-frequency doubled Nd:YAG laser, equipped with a HelEx sample cell, and the cyclone extraction sample cup concentric with the CCD camera can move in the large sample cell of 260x260mm to extract ablation aerosol, with a maximum output of 20Hz, 20.48J cm -2 , and the customized sample cell prepared by 3D printing can measure multiple non-standard shaped samples at the same time, and this sample cell allows transmitted light to pass through, so that some samples can maintain their colors under the CCD without distortion; the 193nm laser ablation system is RESOlution M-50-LR—Coherent 102 (maximum repetition rate of 100Hz). The laser pulse width is 20ns, and the maximum pulse output energy is 200mJ; the laser wavelength is 193nm, the frequency is 1-20Hz, and it can be continuously adjusted online. The highest energy density measured on the sample surface is 30J cm -2 .
[0055] The laser ablation system is preheated for 20 minutes before use. During this period, the sample cup and the ablation cell are evacuated and purged with high-purity helium. Before analyzing the sample, the NIST610 glass standard is used to tune the instrument, and the parameters are adjusted to obtain the maximum signal intensity value and the minimum relative standard deviation (RSD) of the elements to be measured (mainly rare earth elements such as Sc, Y, La, etc.).
[0056] Example 1. Determination of the mineral polymer ratio
[0057] 1. Calculation of the curing system ratio
[0058] In the geopolymers, Al is provided only by metakaolin; Si is provided by metakaolin, sodium silicate solution, and quartz (in some formulations); Na is provided by sodium silicate solution and sodium hydroxide; and H2O is provided by sodium hydroxide, sodium silicate solution, additive element mother liquor, and pure water (added in some formulations).
[0059] Therefore, based on the corresponding contents of each atom, Table 1 can be listed as follows:
[0060] Table 1 Element contribution table of each component (in mol)
[0061] Relative molecular mass (M) 39.998 400 60.08 222.12 18.016 NaOH water glass quartz metakaolin MilliQ Na 1 1.368 - - - Si - 1.764 0.968 1.940 - Al - - - 1.462 - <![CDATA[H2O]]> 0.5 14 - - 1
[0062] In the table, NaOH, water glass, quartz, metakaolin, and MilliQ represent the five components of sodium hydroxide, sodium silicate, quartz powder, metakaolin powder, and additional pure water, respectively. During the experimental stage of the curing system, the element solution is not added temporarily.
[0063] Therefore, when designing the formulation of the present invention, assuming that the only source of n(Al)=1, combined with the calculation formula of the M value, the following system of equations can be obtained:
[0064]
[0065] By giving three key ratios of M, n(Na) / n(A), and n(Si) / n(Al), the proportions of the only four components can be solved, and the weighing mass can be calculated according to the relative molecular mass. In addition, the addition amount of pure water (MilliQ) is used to simulate the mass of water introduced by the additive element mother liquor, and this content needs to be calculated through the water loss of the dried sample and the target concentration.
[0066] 2. Research on the curing formulation of geopolymers
[0067] According to the system of equations (1), geopolymers formulations with corresponding ratios can be designed within the common key parameter range of the formulations. Then, three formulations were experimentally tried, and their weighing results are as follows, which are respectively marked as GP-1, GP-2, and GP-3. The specific weighing data are shown in Table 2 below:
[0068] Table 2 Addition amounts of each component of the trial-produced geopolymers
[0069]
[0070] The three groups of samples respectively simulate the possible situations encountered in the formulation adjustment within the common ratio range. GP-1 represents the situation of high silicon-aluminum ratio and high alkalinity, GP-2 represents the situation of low silicon-aluminum ratio and high alkalinity, and GP-3 represents the situation of low alkalinity.
[0071] After weighing and adding each component of the three groups of samples into a plastic beaker, the samples were stirred using a double-screw electric stirrer. Stir for more than 2 h at a speed of 700 r / min (500 r / min for GP-3 to prevent splashing). After aging for more than 12 h, pour into a mold. All three slurries have fluidity and can self-level in the mold, proving that the slurry is relatively stable at room temperature. Then, place the mold in an oven and dry it continuously at 80 °C, and measure the weight loss of the samples after 12 h and later. The moisture content after drying to a constant weight is shown in Table 3.
[0072] Table 3 Drying weight loss of GP-1, 2, and 3 (g)
[0073] Mold weight Adding slurry 12h 14h 16h 18h Moisture content GP-1 135.19 583.59 509.56 509.61 509.54 509.51 8.61% GP-2 181.23 386.07 299.81 298.55 298.40 298.48 9.26% GP-3 181.36 412.79 355.78 335.72 335.73 335.68 8.52%
[0074] It can be seen that all slurries are in a constant weight state after drying at 80 °C for 14 h. Select the GP-3 sample and raise the drying temperature to 110 °C after drying to a constant weight. After cooling, the weighing fluctuation is less than one-thousandth, and it can be considered that the slurry no longer loses water. From this, the water loss rate of the slurry in the whole range is calculated to be 9.20% ± 1.09% (n = 3), and the expected element solution ratio is calculated based on this water loss rate in subsequent experiments.
[0075] 3. LA-ICP-MS analysis
[0076] The 213 nm laser ablation system in the present invention has advantages in processing non-standard shaped samples and identifying colors. Therefore, the nodule samples were fixed on the sample plate with Blu Tack and subjected to LA-ICP-MS analysis, as Figure 1 shown.
[0077] From Figure 1 it can be seen that different colored patches on the surface of the nodules are clearly shown under the CCD, appearing as blue patches (20 - 100 μm) in a brownish-black continuous matrix. To determine the relationship between this phenomenon and the elemental composition of the sample, line-scan ablation of the sample was carried out using a 100 μm spot under the set laser parameters, and all elements of the sample were monitored during the process. Due to the too high signal intensity of Na, the detector was saturated and could not be monitored. Therefore, the signal fluctuations of the other two major elements in the sample, namely Si and Al, are shown in the figure. To compare the signal fluctuations of the two elements, the intensity of the lower Si was increased by 20 times to maintain similar values.
[0078] The results show that the fluctuation behaviors of the two elements are basically the same, but the Si / Al ratio is generally higher in the blue area, that is, the Si content in the patch part is higher. This is related to the addition of quartz powder with a higher Si content, because no patches were observed in the GP-2 sample.
[0079] And this phenomenon indicates that in the traditional geopolymer system, quartz as a backbone material fails to be completely dissolved, and the relatively enriched patches of Si content it induces in the final cured sample. Patches of this scale are often referred to as nuggets in studies on the homogeneity of relevant markers. Such nuggets are helpful for the development of the initial strength of geopolymers because during the process of the gel system transforming from liquid to solid, they provide additional sites for gel growth, and in the final cured product, as composite particles in the continuous matrix, they play a role in dispersing the energy at the crack tip. However, in this study, this mechanism has caused a gradient concentration of ions, resulting in uneven element distribution. Therefore, to avoid the influence of similar phenomena on the uniformity of added elements, in the present invention, preferably, n(Qaurtz) = 0.
[0080] Example 2. Preparation of Geopolymer
[0081] 1. Mixing and Curing Process
[0082] When the slurry is in the liquid mixing stage, add the multi-element mother liquor and mix evenly in the liquid state.
[0083] 1) Mixing Method
[0084] At the preset concentration value, each rare earth element starts to precipitate when the pH value is greater than 8.5. Therefore, the element mother liquor should be avoided from being mixed with the alkaline water glass solution or sodium hydroxide prematurely to avoid the formation of white precipitates.
[0085] For the same reason, in order to avoid too high instantaneous alkali concentration and local heating during system mixing, prepare a high-concentration solution of about 12.5M NaOH. The specific operation is as follows: Weigh 202.89g of sodium hydroxide particles by the incremental method, add 400ml of ultrapure water to a plastic beaker and place it in a water bath. Then add the sodium hydroxide particles to the beaker and seal it with a plastic film. After the solution is completely clear and cooled, transfer it to a disposable bottle. Therefore, the mass fraction of water molecules contributed by this solution is 73.9%.
[0086] Accordingly, the present invention sets the following mixing scheme:
[0087] A. Weigh and add the predetermined weight of metakaolin powder and the element mother liquor (some samples need to additionally add ultrapure water) in plastic cup A in sequence, and mix well with an electric stirrer. Since the viscosity of the slurry is relatively high at this time, it is necessary to gradually increase the speed and stabilize at 400r / min and keep it for 2h.
[0088] B. Weigh and add the predetermined weight of water glass solution and sodium hydroxide solution in plastic cup B in sequence, shake well and let it stand for 2h until the solution temperature returns to room temperature, then it can be used as the alkali activation solution.
[0089] C. Under the manual stirring state, add the mixed alkali activator solution to plastic cup A in 5 equal - volume portions. A sharp increase in viscosity should be observed when adding the alkali activator solution for the second time, and it gradually decreases when adding subsequent alkali activator solutions.
[0090] D. Increase the speed of the electric mixer to 600 r / min to ensure that all the slurry is stirred. After maintaining for 2 h, inject the slurry into the mold for subsequent curing.
[0091] The state of the slurry when adding the alkali activator successively can be seen Figure 3 。
[0092] According to the above - mentioned process, without adding quartz powder, the ratio ranges of GP1 - 3 were compromised, and the following formula was designed, marked as GP - 4. The weighing process is shown in Table 4.
[0093] Table 4 Weighing weights of GP - 4
[0094] MK+REE WG+NaOH Dosage Weighing Dosage Weighing Cup 50.18 Cup 49.8 MK 122.8 172.98 WG 215.62 265.42 REE 82.05 255.03 NaOH 11.92 277.34 Rod 102.37 357.4 MilliQ 29.7 387.1
[0095] Calculated, Na / Al = 1.28, Si / Al = 2.50, M = 1.83.
[0096] 2) Pretreatment before curing
[0097] After the stirring is completed, the slurry needs to be degassed to remove defects such as air bubbles introduced during the stirring process of the sample, so as to reduce the voids in the cured sample. Therefore, divide the slurry into three equal parts and inject them into plastic molds, and treat them by vacuum degassing, ultrasonic degassing, and static settling for 20 min respectively, and then place them in an oven at 80 °C for curing.
[0098] After the sample is cured, peel off the bulk on the sample surface, fix it on Blu - Tack, and stuff it into a self - made sample ring to form a sample block of standard size, and place it under a 193 - nm laser ablation system for testing to reveal the elemental distribution information of the sample at a smaller spot scale. Use a 30 - μm spot for testing, and the scanning speed is 5 μm / s -1 。
[0099] It can be seen that through the self - leveling of the slurry, the surface of the sample has reached visual smoothness. Repeat the measurement of three groups of line scans for each sample. Using the previously developed NIM - 4 fused - fired glass external standard, the results after internal calibration with Al element as the internal standard for all samples are shown in Figure 5 。
[0100] It can be seen that the vacuum degassing effect is much better than the other two degassing methods. It is speculated that this phenomenon is related to the smaller particle size of the raw materials. For similar powders, during the wetting process, it is mainly hindered by the gas adsorbed on the powder surface. Therefore, when the air pressure is reduced, the gas on the powder surface is discharged and the powder is completely wetted. This avoids particle agglomeration during the curing process, thereby greatly improving the elemental uniformity of the cured sample. Therefore, during the two processes of discharging gas from the powder sample, namely, the mixing stage of the elemental mother liquor and metakaolin powder, and after the sample is stirred, it is necessary to perform corresponding vacuum degassing (dissolution) steps. Comparing the measured elemental signal stability with the results of the glass matrix NIM-4, it can be seen that the signal stability level of the samples in the Vacuum group is close to that of the fired glass samples. The relative standard deviation (RSD) of the Si / Al signal ratio of NIM-4 is 1.2% (n = 95, k = 1), while that of the samples in the Vacuum group is 3.1% (n = 96, k = 1). The remaining data are shown in Table 5.
[0101] Table 5 Comparison of signal stability between the samples in the Vacuum group and NIM-4 samples
[0102] NIM-4 Total N RSD Vacumn Total N RSD 29Si(IS) 95 1.25% 29Si(IS) 96 3.11% 45Sc(IS) 95 13.71% 45Sc(IS) 96 7.22% 89Y(IS) 95 5.06% 89Y(IS) 96 8.31% 139La(IS) 95 5.02% 139La(IS) 96 6.59% 140Ce(IS) 95 4.89% 140Ce(IS) 96 7.57% 141Pr(IS) 95 4.95% 141Pr(IS) 96 7.38% 146Nd(IS) 95 6.87% 146Nd(IS) 96 10.19% 147Sm(IS) 95 6.87% 147Sm(IS) 96 12.87% 153Eu(IS) 95 4.55% 153Eu(IS) 96 7.78% 157Gd(IS) 95 7.12% 157Gd(IS) 96 12.53% 159Tb(IS) 95 4.42% 159Tb(IS) 96 7.68% 163Dy(IS) - Not added 163Dy(IS) 96 9.95% 165Ho(IS) 95 4.54% 165Ho(IS) 96 7.38% 166Er(IS) 95 5.66% 166Er(IS) 96 9.23% 169Tm(IS) 95 4.66% 169Tm(IS) 96 6.85% 172Yb(IS) 95 5.47% 172Yb(IS) 96 10.18% 175Lu(IS) 95 4.75% 175Lu(IS) 96 6.85%
[0103] Among them, due to the low signal-to-noise ratio of the Sc element, the measurement effect is not good. It can be seen from other elements that the relative content of the samples is relatively low, which may be the reason for the relatively large RSD obtained. However, the RSD of the Si / Al signal ratio is relatively large, indicating that the two components constituting the matrix in the sample, namely metakaolin and water glass (Si gel), are not completely mixed evenly. This shows that there is still room for improvement in the sample uniformity.
[0104] However, for the samples cured in the mold, a visible demarcation line can be observed on the longitudinal section between the surface and the interior of the sample, such as Figure 6 .
[0105] It can be seen that the internal structure of the sample is loose and accompanied by cracks. This phenomenon is related to the capillary action during the water loss process of the sample slurry. This phenomenon is similar to the slip casting process of ceramics, that is, at the initial stage of curing, the water loss rate of the outermost layer of the sample is the fastest, which drives smaller particles to form a thin wall layer on the surface of the sample; after the thin wall layer is formed, the water is still evaporating. At this time, the thin wall layer forms a filter plate. As the thin wall layer thickens, the resistance to water diffusion gradually increases; when the water loss inside the system reaches the limit, the entire slurry begins to shrink and internal stress is generated due to the difference in shrinkage rates between the inner layer and the outer layer, eventually forming cracks.
[0106] To confirm the differences between the surface and the interior of the sample, internal parts with different visual colors were taken, fixed on the sample ring, and subjected to the same LA-ICP-MS analysis. The results are shown in Figure 7. It can be seen that as the structure of the sample becomes more porous, more voids are introduced, leading to a decrease in its measurement stability. Also, more large particles generated during ablation can be observed in the CCD camera of the laser ablation system. Therefore, to prepare a completely micro-region homogeneous sample, a more microscopic forming process is required.
[0107] 2. 3D printing forming process
[0108] The present invention adopts the 3D printing forming method, which is characterized by "additive manufacturing", that is, by successively adding materials point by point, line by line, and layer by layer on the substrate and curing them on the printed sample, finally forming a three-dimensional entity. When applied to the geopolymer system, different from the traditional integral injection molding, it is changed to form each solid unit one by one. The original centimeter-level long curing scale is divided into multiple short-time forming processes at the scale of hundreds of micrometers, thereby suppressing the differentiation phenomenon between the surface layer and the inner layer of the sample, and thus achieving the overall uniformity of the sample.
[0109] 1) Direct writing forming process
[0110] Considering the reaction mechanism of the above geopolymer system, the use of the slurry direct writing (DIW) technology can meet the requirements of its 3D printing. As a common technology for 3D printing ceramics, the DIW technology extrudes the ceramic slurry from the barrel through an extrusion device, extrudes it through the nozzle at the specified position, and moves on the two-dimensional plane according to the path setting. After completing the sliced pattern of this layer, the barrel is raised or the platform is lowered to the appropriate position to perform the printing of the next layer, and so on until the printing is completed to obtain a three-dimensional entity.
[0111] The whole process depends on the rheological properties of the slurry, that is, during the extrusion process, it changes to a fluid under the action of external force and quickly "solidifies" after extrusion to maintain the shape without collapse, so as to retain the formed shape to the greatest extent and separate the extruded part from the subsequent slurry. And, in order to make the best use of the characteristic of the geopolymer system losing water and curing, the present invention adopts the SYNO 4070 ceramic printer (Henan YuancuangaoKe Technology Co., Ltd., Figure 8 ) which has the function of environmental heating and can turn on the internal hot air circulation during the curing process, so that the extruded slurry can lose water faster. And, a motor-driven stirring screw ( Figure 9 Figure a in it) is installed in the extrusion head ( Figure 9 Figure b in it), which can provide shear force to temporarily reduce the kinematic viscosity of the gel system, so as to extrude more smoothly. It can be seen that the slurry is tightly filled in the screw without voids and can remain wet inside the extrusion head, which helps to maintain the stability of the slurry before extrusion.
[0112] 2) Optimization of alkali activation concentration
[0113] The concentration (alkalinity) of the alkali activator determines the dissolution degree of the raw material particles (metakaolin powder), and at the same time determines the viscosity change and curing rate of the slurry system. Therefore, to further improve the uniformity of the sample, it is necessary to increase the concentration of the alkali activator. However, some studies have shown that too high an alkali content will cause excessive surplus alkali after curing, and phenomena such as "efflorescence" will occur during storage, resulting in the precipitation of local elements, which is actually unfavorable for maintaining elemental uniformity. Therefore, it is necessary to optimize the concentration of the alkali activator.
[0114] However, after confirming that no inert filler (quartz powder) can be added to the geopolymer system in the present invention, the degree of freedom of the system decreases, resulting in only two of the three parameters of Si / Al, modulus M, and Na / Al being freely adjustable. Therefore, with the Si / Al of the sample fixed at 2.50, the concentration of NaOH was gradually increased while reducing the addition amounts of the water glass solution and metakaolin powder. In this way, while the M value gradually decreases, no additional free water is introduced into the system, but inevitably the Na / Al value will increase.
[0115] Based on this scheme, samples with a gradient alkali activation concentration were set in the present invention as shown in Table 6, and labeled as GP-M1 to GP-M10.
[0116] Table 6 Variation of the geopolymer ratio with different M values
[0117] Dosage of NaOH solution M S / L GP-M1 52.73 1.72 0.37 GP-M2 59.16 1.65 0.37 GP-M3 65.50 1.58 0.37 GP-M4 71.76 1.51 0.36 GP-M5 77.94 1.45 0.36 GP-M6 84.05 1.40 0.35 GP-M7 90.07 1.34 0.35 GP-M8 96.02 1.29 0.34 GP-M9 101.89 1.25 0.34 GP-M10 107.69 1.20 0.34
[0118] To exclude the influence of the decrease in the solid-liquid ratio (S / L) on the curing ability of the polymerization system, the samples were respectively poured into molds. And a syringe was used to apply three parallel thin layers of slurry under the molds to simulate the slurry extrusion process during 3D printing. Then the whole was placed in an oven for 150 s to observe its curing situation, as Figure 10 shown.
[0119] It can be seen that starting from GP-M7, the thin-layer samples could not cure within the specified time and local agglomeration of droplets occurred, corresponding to the decrease in wettability and printing processability. The gel system formed by too high a Na content and too low a solid-liquid ratio was difficult to maintain the wetting state with the bottom of the mold, which would exacerbate shrinkage during the curing process, resulting in more internal cracks.
[0120] Subsequently, the slurry in the molds of GP-M1 to GP-M10 was cured, and then the surface samples were peeled and placed in a self-made sample cell for LA-ICP-MS analysis. The signal stability of rare earth elements was represented by the lanthanum (La) element, and the results are as Figure 11 shown.
[0121] As can be seen from the figure, consistent with the conclusion of the curing performance, the signal stability of the GP-M5 to M10 slurries gradually deteriorates, and severe signal fluctuations occur in the M10 slurry, which may be related to the severe shrinkage of the slurry itself, resulting in potential cracks inside the final cured sample.
[0122] Based on the above conclusions, the formulation of GP-M4 exhibits good curing performance and LA-ICP-MS signal stability and is used for subsequent research.
[0123] 3) Shear viscosity change
[0124] In the initial stage of the geopolymerization reaction, the tetrahedra are gradually dissolved by the alkali activator in the system to form a loose gel network. As the dissolution amount gradually increases, the connectivity of the gel network increases and the free water decreases, resulting in a gradual increase in viscosity and finally curing. To quantitatively describe the rheological property changes of the slurry during this process and thus determine the appropriate printing time and viscosity, an Anton Paar ViscoQC100-H viscometer was used in the experiment to monitor the change of the sample viscosity with time. The V73 blade was used in the experiment, and the maximum test viscosity was 20.48 Pa·s (200 r min -1 ), and the accuracy was one-thousandth.
[0125] The slurry with the GP-M4 formulation was mixed, and the slurry was taken out of the slurry and placed in a PFA tube every 2 h, continuously stirred at the maximum speed until the reading was stable, and the results were recorded three times. The average value and standard deviation (1 s) are as Figure 12 . It can be seen that the slurry was about 0.32 Pa·s when continuously stirred for 28 h, and an obvious increase in viscosity was observed. It reached 1.34 Pa·s at 36 h and then started to increase sharply. After 39.5 h, it was partially solidified at the rotation speed of the viscometer and could not be accurately measured. The final viscosity reached 8.76 Pa·s.
[0126] After testing, the slurry can be kept in the extrusion head without leakage at a viscosity of 0.16 Pa·s. At the same time, in order to dissolve as many raw material particles as possible, the most suitable starting printing time should be controlled between 26 h and 38 h after the start of sample stirring, that is, at least 26 h and at most 38 h. After that, the viscosity of the sample increases sharply and it will be difficult to maintain fluidity until printing is completed. Considering the time-consuming of the subsequent 3D printing forming process, the preferred stirring time for this time is 26 h.
[0127] 4) 3D printing optimization
[0128] Even between 26h and 38h, the viscosity of the slurry varies by as much as 20 times. For slurries with different viscosities, each has its own advantages and disadvantages. High-viscosity slurries can better retain their shape after extrusion and require less curing time. However, they have the drawbacks that a greater pressure and screw rotation speed are needed for extrusion, and phenomena such as pipe blockage and local curing before extrusion may occur. Low-viscosity slurries have a relatively higher free water content, resulting in poorer forming accuracy after extrusion during printing and requiring a longer curing time. Their advantages are that they have a higher tolerance to problems such as extrusion head overheating and pipe blockage, and can be extruded at lower pressures and screw rotation speeds. Therefore, the printing slurries are printed separately at 26h and 38h and labeled GP-M4-LV and GP-M4-HV to represent the printing effects of low- and high-viscosity slurries.
[0129] The 3D printing model was constructed using SolidWorks 2018, exported as an STL format, and imported into the Ultimaker Cura software to be sliced into a gcode format file. The slicing path is shown as Figure 13 shown.
[0130] According to the density of the sample filled on the substrate, key parameters in the slicing need to be designed and matched, such as layer thickness, extrusion head aperture, trace width, filling density, extrusion flow rate, etc. After optimizing the optimal parameters for the two slurries with different viscosities, they were printed separately. And the samples were analyzed by LA-ICP-MS to show the micro-area uniformity of the elements.
[0131] Obviously, GP-M4-LV shows better signal stability, as Figure 14 shown. Therefore, it is determined that the slurry should be printed at a relatively lower viscosity, that is, 26h is preferred.
[0132] In addition, to facilitate the transfer of the sample from the substrate to the oven and subsequent storage, a sample ring with a standard size was designed. And finally, according to the optimized process route determined in each step, the chimeric printed sample was prepared without oven drying and labeled GP-M4-LV-FINAL( Figure 15 ). It can be seen that the surface of the sample is smooth and meets the requirements of micro-area analysis.
[0133] Example 3. Verification of Micro-Area Uniformity of Geopolymer Samples
[0134] 1. Overall Micro-Area Imaging of a Single Piece Sample
[0135] Example 2 prepared a GP-M4-LV-FIANL chimeric sample. It is necessary to characterize the micro-region uniformity of the sample. However, since the overall size (cm) of the sample is much larger than the scale (μm) of in-situ micro-region analysis, if adjacent measurements are made on the whole sample, the required measurement time is too long, and the results will be greatly affected by changes in measurement conditions and instrument sensitivity drift. Therefore, in order to shorten the measurement time, a measurement strategy as shown in Figure 16 was designed:
[0136] The measurement process performs line scanning in the order of the numbers in the figure. In this way, the sample is divided into 12 equal-sized regions every 30°. And based on the measurement data on 12 lines, the concentration values of the regions of the sample that are not actually measured within the same radius range are simulated by the TPS (Thin Plate Spline) interpolation method. In addition, at the central position of the sample, the laser ablation paths are too close to each other, so interference is inevitable. Therefore, the data at the middle position of the sample piece is omitted.
[0137] For the measurement results of the GP-M4-LV-FINAL sample, a polar coordinate heat map was plotted using Origin 2018 as shown in Figure 17 . The element order in the figure is arranged according to the element order in Table 7, starting with Sc and ending with Pb; the coloring rule in the figure is that the high-concentration end is blue, the low-concentration end is red, and the intermediate color is green. The color blocks exceeding the upper and lower limits are gray and black respectively. Therefore, the uniformity of the elements can be visually determined by the color distribution in the figure. It can be seen that the added elements are evenly distributed in the GP-M4-LV-FINAL sample.
[0138] Table 7 Determination results of rare earth element mother liquor concentration
[0139]
[0140]
[0141] 2. Local micro-region imaging of the sample
[0142] After verifying the uniformity of the sample on a large scale, random sampling can be carried out, and the uniformity of smaller micro-regions of the sample can be tested according to the traditional element concentration imaging method. That is, LA-ICP-MS analysis is performed on the regional sample through adjacent line scanning, and staining imaging is performed according to the signal intensity values of the corresponding elements in the line scanning. The scanned area covers a regional position in the range of about 400*700μm, which is the same as the rectangular position in Figure 16 . NIM-4 is used as a quality control sample for the data, and time drift correction is performed. The remaining arrangement and data processing methods are the same as those in Figure 17 , and the results are as shown in Figure 18 .
[0143] It can be seen that it is consistent with the results of the elemental concentration imaging map of the whole sample, and the elements show good uniformity in LA-ICP-MS analysis. However, for individual elements such as Yb and Pb in the above LA-ICP-MS analysis, some "false" patches are shown, and this phenomenon gradually intensifies with the decrease of the relative signal intensity (compared with the internal standard element) and the signal-to-noise ratio. A more appropriate correction scheme should be found to weaken this influence. However, in the present invention, there are no other internal standard elements, so the RSD values of each element in the representative line scan are given for reference (Table 8).
[0144] Table 8 Fluctuation of each element in the representative line scan (n = 18)
[0145]
[0146]
[0147] Based on the above analysis, the present invention has established a process route for developing reference materials based on geopolymers, that is, based on three types of components: gelling active components, elemental mother liquor, and alkali activators, and through four main steps of raw material ratio, component mixing, pre-curing treatment, and curing and forming to prepare an artificially synthesized mineral polymer sample added with target elements.
[0148] In the raw material ratio stage, it is necessary to measure the elemental content of each raw material component and make the ratio according to the results, so as to control the three key parameters of the silicon-aluminum ratio (Si / Al), sodium-aluminum ratio (Na / Al), and alkali activation modulus (M) in the formed sample. In this study, the determined ratios are Na / Al = 1.28, Si / Al = 2.50, and M = 1.83 (3D printing and curing) respectively.
[0149] The component mixing method should adopt the pre-mixing method. In the present invention, it is the mixing of metakaolin and elemental solution, and the mixing of sodium silicate solution and sodium hydroxide solution, and then mixing in batches after stabilization. And the addition of quartz (spinal material) components should be avoided, because it cannot be completely dissolved during the gel polymerization process, resulting in nodules in the final cured sample and affecting the uniformity.
[0150] In the pre-curing treatment process, that is, degassing the sample slurry is necessary, and the vacuum degassing method is significantly better than the ultrasonic degassing or static degassing. In the curing and forming stage, the injection molding method will cause the formation of a boundary line between the wall layer and the inner layer of the sample and affect the uniformity inside the sample. The 3D printing and forming method can print the sample into the sample ring at a lower viscosity by dividing the slurry and form a smooth thin slice sample.
[0151] The sample after process route optimization (GP-M4-LV-FINAL) was analyzed by LA-ICP-MS to verify good internal homogeneity. The relative standard deviation in LA-ICP-MS measurement was 3.82% - 7.35% (after internal standard correction), which was at the same level as the measurement accuracy of the NIM-4 sample prepared by the fused glass method.
Claims
1. A preparation method of a highly uniform mineral polymer doped with inorganic elements, comprising the following steps: S1. Determine the dosages of each raw material according to the equations shown in formula (1); In the formula, n(NaOH) represents the molar amount of sodium hydroxide, n(Water glass) represents the molar amount of water glass, n(metakaolin) represents the molar amount of metakaolin, n(Na) / n(Al) represents the molar ratio of sodium element and aluminum element in the system, and n(Si) / n(Al) represents the molar ratio of silicon element and aluminum element in the system; M represents the modulus of the alkali activator, which is used to describe the molar ratio of the corresponding oxides of Si and Na in the alkali activator, and its calculation formula is as follows: M = n(SiO2) / n(Na2O) S2. Under the condition of stirring, add the alkali activator solution to the mixture of metakaolin and the target element mother liquor in multiple times, and cure the obtained slurry.
2. The preparation method according to claim 1, characterized in that: n(Na) / n(Al) = 1.28, n(Si) / n(Al) = 2.50, M = 1.
83.
3. The preparation method according to claim 1 or 2, characterized in that: In step S2, after the addition of the alkali activator solution is completed, stir at a rotation speed of 400 - 600 r / min for 26 - 38 h.
4. The preparation method according to any one of claims 1-3, characterized in that: In step S2, before the curing, degas the slurry.
5. The preparation method according to claim 4, characterized in that: The degassing treatment method is vacuum degassing; The time of the vacuum degassing is 15 min, and the air pressure is pumped to below 0.01 Mpa.
6. The preparation method according to any one of claims 1-5, characterized in that: In step S2, the curing method is 3D printing molding.
7. The preparation method according to claim 6, characterized in that: The 3D printing molding is carried out 26 - 38 h after the stirring of the slurry.
8. The preparation method according to any one of claims 1-7, characterized in that: Use the LA-ICP-MS method to test the uniformity of the mineral polymer.
9. A mineral polymer prepared by the method according to any one of claims 1 - 8.
Citation Information
Patent Citations
Method for preparing synthetic mineral particles
CN108473323A
Ultrahigh strength geopolymer based material and preparation method thereof
CN110510933A